EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN PENDEKATAN QUANTUM LEARNING PADA POKOK BAHASAN STATISTIKA DITINJAU DARI MINAT BELAJAR SISWA KELAS XII SMK KELOMPOK TEKNOLOGI SE-KABUPATEN KEBUMEN TAHUN PELAJARAN 2012/2013 - Rizana, Dani (Jurnal Pembelajaran Matematika, 2013)
AbstractThe objective of this research is to investigate: (1) which of the TPS learning model with Quantum Learning approach, the TPS learning model, and the conventional learning model results in a better learning achievement of the students; (2) which of the students with the high, medium, and low learning interest levels have a better learning achievement; (3) which of the students taught in the TPS learning model with Quantum Learning approach, the TPS learning model, and the conventional learning model have a better learning achievement with the high, medium, and low learning interest levels; and (4) which of the students have a better learning achievement in each of the learning interest levels with the TPS learning model with Quantum Learning approach, the TPS learning model, and the conventional learning model. This research used the quasi-experimental method with the factorial design of 3 x 3. The population of this research was all of the 12th-grade students of the engineering vocational secondary schools in Kebumen regency in the academic year of 2012/2013. The data of this research were gathered through documentation, questionnaire, and achievement test. The test on the hypothesis of the research was conducted by using unbalanced Two-way Analysis of Variance. The results of this research are as follows: (1) the TPS learning model with Quantum Learning approach and the TPS learning model result in an equal learning achievement whereas the TPS learning model with Quantum Learning approach results in a better learning achievement than the conventional learning model. However, the TPS learning model and the conventional learning model result in an equal learning achievement; (2) the students with the high learning interest level have an equal learning achievement to those with the medium and low learning interest levels; (3) the TPS learning model with Quantum Learning approach results in an equal learning achievement to the TPS learning model but results in a better learning achievement than the conventional learning model in the high, medium, and low learning interest levels whereas the TPS learning model results in an equal learning achievement to the conventional learning model in the high, medium, and low learning interest levels; and (4) the students with the high learning interest level have an equal learning achievement to those with the medium and low learning interest levels in the TPS learning model with Quantum Learning, the TPS learning model, and the conventional learning model.Keywords: Learning achievement, TPS, Quantum Learning, conventional, and learning interest